History of Katerinoslav histological school (to 100 years anniversary of histology department of Dnipropetrovsk medical academy). Part I: 1917-1962 - D. G. Marchenko; S. B. Morozova; N. S. Petruk; O. Yu. Pototska; L. A. Romanenko; N. V. Stanishevska; N. M. Sultanova; L. A. Filimonova; I. S. Khripkov; K. M. Shevchenko; I. V. Tverdokhlib (Морфологія, 2017)
The birth of a science school is always the result of the efforts and efforts of a great scientist and celebrity. Such a scientist - the founder of the Ekaterinoslav histological school - was Professor Vladimir Porfyriyovych Karpov.